ChemInform Abstract: Deuterodehalogenation — A Mild Method for Synthesising Deuterated Heterocycles. Issue 45 (23rd October 2014) - Donald, Craig S.; Moss, Thomas A.; Noonan, Gary M.; Roberts, Bryan; Durham, Emma C.
Abstract Optimized reaction conditions including 2‐propanol‐d8 as the deuterium source are developed for the deuterodehalogenation of various bromo‐ and chloro‐substituted heterocycles.